The occurrence of germline BRCA1 and BRCA2 sequence alterations in Slovenian population - Hočevar Marko; De Grève Jacques; Teugels Erik; Žgajnar Janez; Krajc Mateja; Stegel Vida; Novaković Srdjan (BMC, 2011)
Abstract Background The BRCA1 and BRCA2 mutation spectrum and mutation detection rates according to different family histories were investigated in 521 subjects from 322 unrelated Slovenian cancer families with breast and/or ovarian cancer. Methods The BRCA1 and BRCA2 genes were screened using DGGE, PTT, HRM, MLPA and direct sequencing. Results Eighteen different mutations were found in BRCA1 and 13 in BRCA2 gene. Mutations in one or other gene were found in 96 unrelated families. The mutation detection rates were the highest in the families with at least one breast and at least one ovarian cancer - 42% for BRCA1 and 8% for BRCA2. The mutation detection rate observed in the families with at least two breast cancers with disease onset before the age of 50 years and no ovarian cancer was 23% for BRCA1 and 13% for BRCA2. The mutation detection rate in the families with at least two breast cancers and only one with the disease onset before the age of 50 years was 11% for BRCA1 and 8% for BRCA2. In the families with at least two breast cancers, all of them with disease onset over the age of 50 years, the detection rate was 5% for BRCA2 and 0% for BRCA1. Conclusion Among the mutations detected in Slovenian population, 5 mutations in BRCA1 and 4 mutations in BRCA2 have not been described in other populations until now. The most frequent mutations in our population were c.181T > G, c.1687C > T, c.5266dupC and c.844_850dupTCATTAC in BRCA1 gene and c.7806-2A > G, c.5291C > G and c.3978insTGCT in BRCA2 gene (detected in 69% of BRCA1 and BRCA2 positive families).